Kanglaite (Coix Seed Extract) as Adjunctive Therapy in Cancer: Evidence Mapping Overview Based on Systematic Reviews With Meta-Analyses - Lu, Cuncun; Wu, Shuilin; Ke, Lixin; Liu, Fumei; Shang, Wenru; Deng, Xiuxiu; Huang, Yanli; Zhang, Qiang; Cui, Xin; Mentis, Alexios-Fotios A.; Xie, Yanming; Wang, Zhifei (Frontiers in Pharmacology, 2022)
Several quantitative systematic reviews of Kanglaite (KLT), an herb preparation used to treat cancer and malignant pleural effusion, have been published in recent years. However, the clinical evidence reported in these studies has not been pursued further and the methodological quality of these meta-analyses remains unknown. Therefore, an overview was designed to map the evidence landscape based on the published meta-analyses on KLT in cancer treatment. Two bibliographic databases (PubMed and Embase) were searched from inception to November 25, 2021. Two independent reviewers were involved in study selection, data abstraction, and methodological quality assessment using AMSTAR 2. The principal features of publications and the clinical outcomes of efficacy and safety were synthesized narratively, and results of methodological quality were reported as frequencies and percentages with the corresponding 95% confidence intervals. The evidence map was used to visualize the overall quality. Excel 2016 and Stata 17/SE were used for data analysis. Thirteen meta-analyses published in English were included for in-depth analysis. Among them, the year of publication ranged from 2008 to 2021, and the number of included patients ranged from 488 to 2,964. Regarding the cancer type, seven articles focused on non-small-cell lung cancer, two on malignant pleural effusion, and four reviews on digestive system malignancies, such as hepatocellular carcinoma and pancreatic cancer. Almost all included meta-analyses reported that KLT as adjunctive therapy could improve various efficacy outcomes (such as disease response rates, quality of life, immune indicators) and reduce the rate of occurrence of adverse reactions, such as nausea and vomiting, leukopenia, and anemia. In terms of their methodological quality, three meta-analyses were of low quality, whereas 10 studies were critically low in quality. The methodological flaws main involved items 2 , 3 , 4, 5 , 7 , 8 , 10, and 12 based on the AMSTAR 2 tool. Current evidence reveals that KLT is effective and safe as adjunctive treatment for non-small-cell lung cancer, malignant pleural effusion, and digestive system malignancies (such as hepatocellular carcinoma). However, the results assessed in this overview should be further verified using well-designed and clearly reported clinical trials and meta-analyses of KLT.